Y chromosome polymorphism in Turkish patients with reproductive problems: a genetic centre experience - Atlı, Emine İkbal and Mail, Çisem and Gurkan, Hakan and Yalçıntepe, Sinem and Demir, Selma and Atlı, Engin (The European Research Journal, 2023)
Objectives: Male infertility is a large and unexplored global health problem in terms of prevalence. Chromosomal polymorphisms may be associated with infertility and recurrent spontaneous abortions. Non-protein coding and frequently repetitive satellite DNA sequences are found in these regions. Methods: This study aims to present a genetic laboratory experience in the evaluation of frequency, type and significance of Y chromosome polymorphism of Turkish patients with reproductive system problems. The study included 435 patients aged 18-60 years with a documented clinical diagnosis of infertility. Results: In our study, 435 individuals were analyzed cytogenetically and 75 of them (17.24%) were found to carry chromosomally polymorphic variants in Y chromosome. We detected increased heterochromatin structure in the long arm of chromosome Y (Yqh+) as a common variant in our patient group. The frequency of chromosomal polymorphism Yqh- is % 11.26. The rate of chromosomal polymorphism we detected is close to those reported in the literature (10-15%) and statistically significant (p < 0.001), twice that found in the normal population (2-5%). Conclusions: Findings support that Y chromosome polymorphisms may be associated with infertility risk and may play an important role in the development of infertility. More research combining genome studies and other fields is needed to clarify the relationship of Y chromosome polymorphisms with and to infertility.